A “rotating menu” of medical uncertainty for families affected by telomere biology disorders: A qualitative interview study - Emily E. Pearce; Alina Majid; Toniya Brown; Catherine Wilsnack; Camella Rising; Ashley S. Thompson; Rowan Forbes Shepherd; Arman Niknafs; Allison Werner-Lin; Melissa B. Gilkey; Kurt M. Ribisl; Sadie P. Hutson; et al. (SSM: Qualitative Research in Health)
Background: Medical uncertainty may cause distress and challenge medical decision-making for patients with rare diseases and their caregivers. Few studies have examined the experience and management of medical uncertainty in rare disease and the dynamics of multiple medical uncertainty sources, issues, and management strategies. Objective: We explored the experience and management of uncertainty in individuals with telomere biology disorders (TBDs), a set of rare cancer-prone bone marrow failure syndromes, and their caregivers. Design: Participants (N = 32) in this qualitative-descriptive study were individuals with a TBD (n = 17) and/or their caregivers (n = 15). We thematically analyzed transcripts to describe the presence and dynamics of medical uncertainty in TBDs using categories from a previously published taxonomy. Results: Individuals with TBDs and caregivers described medical uncertainty as a chronic burden embodied amidst a range of interrelated sources and issues. Scientific uncertainty included diagnostic and prognostic ambiguity. Practical uncertainty focused on logistical challenges of building and maintaining medical care teams. Personal uncertainty included difficulty realigning self-identity, goals, and relationship expectations post-diagnosis. Scientific, practical, and personal uncertainty issues were entangled. The rarity of TBDs resulted in limited scientific knowledge, which gave rise to practical and personal uncertainties affecting medical decision-making and relationship formation (e.g., creating trusted care teams where patient knowledge of TBDs may exceed that of clinicians). Participants used multiple strategies for uncertainty management, particularly information-seeking and community-building. However, these management strategies could intensify, rather than resolve, participants’ medical uncertainty. Conclusion: In TBDs, medical uncertainty manifests as a network of multiple, interrelated, sources and issues, which require evolving management strategies. Researchers must be mindful that complex, synergistic uncertainty networks contribute to psychosocial challenges in TBDs. Additional research is warranted to address scientific uncertainty in TBDs, including clinical manifestations and underlying biology, and to develop psychosocial interventions that recognize and anticipate evolving uncertainty.